Corruption as Impediment to Good Governance in Nigeria - Abdulhamid Bello, Jamilu; Abdu Bala , Nasiru; Yusuf Ahmad, Abdullahi; Sa’id Sufi , Kabiru; Kabir Ibrahim, Raihana (Kashere Journal of Humanities, Management and Social Sciences, 2022)
This study examined the challenge of corruption as impediment to good governance in Nigeria. Using the main composites of the concepts of good governance that include the legitimacy of the government, the accountability of the public officials, the capacity/competence of government to formulate policies, deliver services to the citizens, and respect for human rights and the rule of law, the study scrutinized the machinery of governance in Nigeria. The study revealed that despite the huge resources put into the implementation of policies geared towards good governance in Nigeria, there have not been visible changes in the living standard of the citizens largely due to gross corruption in almost every sector of the society. Though the phenomenon has received extensive attention from government officials, scholars and interest groups over the years, it is still a cankerworm in the quest for development in Nigeria. The paper concluded that until the issue of corruption is tackled from the Nigerian political and economic scenes, the nation will continue to remain in the shackle of underdevelopment irrespective of her endowed enormous resources.